Analisa Hubungan Faktor Demografis Karyawan dan Lingkungan Kerja terhadap Potensi Penyakit yang Diderita Karyawan PT Ecogreen Oleochemicals Batam - Nyoto Hendy Wijaya; I Nyoman Sutapa (Jurnal Titra, 2013)
This article discuss about correlation between demographic factor of employees and work environment against potential disease suffered by employees. Demographic factor of employees such as job grade, age, weight, and blood pressure. The company wanted to know about description of potential disease suffered by employees based on demographic factor, the correlation between that variables, and know work environment factor which potentially against disease in workplace. Analysis method used Spearman’s Rho Test, Logistic Regression, and Fishbone Diagram. The higher demographic factor cause the disease suffered by employees more dominated by degenerative disease. All demographic factor have a correlation with potential disease suffered by employees, but only 13 from 24 disease have strong correlation. The potential disease suffered by employees also caused by 2 factors from work environment, namely man (employees awareness still lacking) and management (role of company not optimal). This research was ended by doing effectiveness of annual medical check up analysis, namely by eliminating blood glucose test and add USG mammae test. The company should give further attention to employees, such as give a punishment to employees who not wearing PPE, auditing SHE in workspace, improve the infrastructure and provide training for employees about SHE.